2003
DOI: 10.1185/030079903125002540
|View full text |Cite
|
Sign up to set email alerts
|

Utilization patterns and net direct medical cost to Medicaid of irritable bowel syndrome

Abstract: Irritable bowel syndrome was shown to impose an economic burden on the Medicaid program. The cost of treating patients with irritable bowel syndrome is higher than the cost of treating matched ambulatory Medicaid recipients without the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Bell 22 surveyed the North Carolina Hospital discharge database for the calendar year 1998 and reported an average cost per hospital visit of $7709 for patients with diabetic GP, a figure substantially lower that the annual costs for either the MED or GES groups in our study. Similarly, our costs of care for GP are significantly higher than other chronic GI disorders such as IBS where costs are reported in the range of $2952–5908 per year 23 . An argument could be made that cost‐shifting vs cost‐reduction occurred, in terms of the intensity of the medical therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Bell 22 surveyed the North Carolina Hospital discharge database for the calendar year 1998 and reported an average cost per hospital visit of $7709 for patients with diabetic GP, a figure substantially lower that the annual costs for either the MED or GES groups in our study. Similarly, our costs of care for GP are significantly higher than other chronic GI disorders such as IBS where costs are reported in the range of $2952–5908 per year 23 . An argument could be made that cost‐shifting vs cost‐reduction occurred, in terms of the intensity of the medical therapy.…”
Section: Discussionmentioning
confidence: 94%
“…A number of studies have demonstrated increased health care costs of IBS patients compared with non‐IBS patients, with indirect and direct annual costs estimated to total up to 30 billion dollars 16 ,. 17 Three recently published studies, two performed in health maintenance organizations 36 , 37 and one in two different Medicaid populations, 38 found that the total costs for health care were approximately 50% higher in patients with IBS than in non‐IBS controls. These studies similarly found that the costs were increased particularly with regard to out‐patient rather than in‐patient services.…”
Section: Health Care Costsmentioning
confidence: 99%
“…Direct costs (excluding prescription and overthe-counter drugs) are estimated to be as high as 10 billion dollars, and indirect costs are approximately 20 billion dollars annually [15][16][17]. Patients with IBS use the healthcare system (eg, physician office visits, diagnostic tests, medications) more often than do patients without IBS, as well as patients with select non-gastrointestinal (eg, migraine headaches) and gastrointestinal disorders (eg, functional dyspepsia, GERD, and inflammatory bowel disease) [18][19][20].…”
Section: Irritable Bowel Syndromementioning
confidence: 99%